MERITOKRASI DAN NETRALITAS APARATUR SIPIL NEGARA (ASN) DALAM PENGARUH PILKADA LANGSUNG - Firman Firman (The Indonesian Journal of Public Administration (IJPA), 2017)
Abstract: This study is about the meritocracy system of bureaucracy and the neutrality of civil state apparatus (ASN) in the face of elections to the elections. In various regions there is always a problem of bureaucratic professionalism issues. Despite the various regulations to regulate ASN to be neutral and independent so that the democratic process in this case direct election of the head of the region can run well. However, this issue is always repeated with different schemes for the lust of power and bureaucrat positions that can be facilitated or lifted / accelerated to occupy positions in the bureaucracy. Various rules and regulations were hit or forced only because they became part of the susceptibility when the pilkada was implemented. A regulation about ASN 2014 is expected to filter spoil system problems or promote a bureaucrat in certain positions only because of proximity or for being a successful team during the electionsKeywords: meritocracy system , bureaucracy, election                                                                                                                                                                                                                                                                                                                                                                                                         Abstrak: Kajian ini tentang system meritokrasi birorkasi dan netralitas aparatur sipil negara (ASN) dalam menghadapi pilkada sampai dengan pilkada usai. Diberbagai daerah selalu muncul persoalan permasalahan profesionalisme  birorkasi. Walaupun sudah lahir berbagai regulasi untuk mengatur agar ASN bisa bersikap netral dan independen agar proses demokrasi dalam hal ini pemilihan langsung kepala daerah bisa berjalan dengan baik. Namun, persoalan ini selalu berulang dengan skema yang berbeda untuk syahwat kekuasaan dan jabatan birokrat yang bisa dimudahkan atau diangkat/dipercepat untuk menduduki posisi dalam birokrasi. Berbagai aturan dan regulasi ditabrak atau dipaksakan hanya karena menjadi bagian suskesi saat pilkada dilaksanakan. Muncul regulasi tentang ASN 2014 diharapkan bisa menfilter persoalan spoil system atau mempromosikan seorang birokrat dalam posisi tertentu hanya gara-gara kedekatan atau karena menjadi tim sukses saat pilkada  Kata kunci: Sistem Merit, Birokrasi, Pemilu  Albrow, M. (1989). Birokrasi, diterjemahkan oleh Rusli Karim dan Totok Daryanto, PT. Tiara Wacana. Jakarta.Alon-Barkat, S., & Gilad, S. (2016). Political control or legitimacy deficit? Bureaucracies' symbolic responses to bottom-up public pressures. Policy & Politics, 44(1), 41-58.Assessment of hierarchical tendencies in an Indian bureaucracy. International Journal of Public Sector Management, 20(5), 380-391Cascio, W. F. (2006). The economic impact of employee behaviors on organizational performance. California Management Review, 48(4), 41-59.Kaufman, H. (1956). Emerging conflicts in the doctrines of public administration. American Political Science Review, 50(4), 1057-1073.Laski, H. J. (2014). Parliamentary Government in England (works of Harold J. Laski): A Commentary (Vol. 9). Routledge.Martini, R. (2010). Politisasi birokrasi di Indonesia. POLITIKA Jurnal Ilmu Politik MIP, 1(1), 67-74.Nadel, M. V., & Rourke, F. E. (1975). Bureaucracies. Handbook of Political Science, 5, 373-440.Rourke, F. E. (1984). Bureaucracy, Politics, and Public Policy. Boston: Little, Brown. RourkeBureaucracy. Politics, and Public Policy1984.Rourke, F. E. (1992). Responsiveness and neutral competence in American bureaucracy. Public Administration Review, 539-546.Setiyono, B. (2012). Birokrasi Dalam Perspektif “Politik & Administrasi” (Vol. 1). NUANSA.Soebhan, S. R. (2000). Model Reformasi Birokrasi Indonesia. Jakarta: PPW LIPI.Sudirman ://makassar.tribunnews.com/2016/08/26/daftar-nama-nama-pejabat-soppeng-yang-baru-dilantik diakses pada tanggal 2/10/2017Thoha, M., & Organisasi, P. (1993). konsep dasar dan Aplikasinya. Jakarta: Rajawali Pers.Thompson, J. D. (1967). Organizations in action: Social science bases of administrative theory. Transaction publishers.Woo, K. H. (2015). Recruitment Practices in the Malaysian Public Sector: Innovations or Political Responses?. Journal of Public Affairs Education, 229-246.Janesick, J., Pinter, J., Potter, R., Elliot, T., Andrews, J., Tower, J., ... & Bishop, J. (2009, August). Fundamental performance differences between CMOS and CCD imagers: part III. In Proc. SPIE (Vol. 7439, p. 743907).